MODEL PEMBELAJARAN KOOPERATIF TEAM ASSISTED INDIVIDUALIZATION (TAI) UNTUK MENINGKATKAN HASIL BELAJAR TEMA TOKOH DAN PENEMUAN SISWA KELAS VI MIN TATABA: MI NEGERI TATABA , KECAMATAN BUKO, KABUPATEN BANGGAI KEPULAUAN - MUHIDIN BAHUK (Mitra Pendidikan, 2022)
This study aims 1). Knowing student learning outcomes in the theme of 3 characters and findings before using the Team Assisted Individualization (TAI) method 2). Knowing student learning outcomes in the theme of 3 characters and findings after using the Team Assisted Individualization method This type of research uses classroom action research (CAR). Classroom action research is research conducted by teachers in their own classrooms through self-reflection, with the aim of improving their performance as teachers, so that student learning outcomes increase (Wardani, 2011). This research was conducted in Class VI MIN Tataba, Buko District, Banggai Regency, Central Sulawesi Archipelago. The reasons for choosing the research location in class VI MIN Tataba are 1). the researcher is a class VI teacher at MIN Tataba so as to facilitate the process of carrying out research 2.). Class VI students of MIN Tataba have homogeneous abilities and it is hoped that the results of the research are truly in accordance with the conditions in the field This research was carried out in the Odd semester of the 2021/2022 academic year for 2 months, namely in August-September 2021. The source of the data for this research was the Class VI students of MIN Tataba in the odd semester of the 2021/2022 academic year, totaling 27 students. In this study, data collection was carried out by direct observation of learning activities in the classroom, then there was also documentation covering aspects of real classroom activities, then learning outcomes tests to determine the learning outcomes of students in class VI MIN Tataba The data analysis technique used in this research is descriptive qualitative. The data analyzed at this meeting included data obtained through observation and documentation. Data obtained from observations are reduced by selecting important data and discarding useless information. This classroom follow-up study is said to be successful if the results of this study are student absorption of 76.00% and completeness of learning outcomes 76.00% Based on the data from the classroom action research, starting from the pre-cycle, Cycle I and Cycle II, it can be concluded that the use of the Team Assisted Individualization Model can increase the learning outcomes of the sixth grade students of MIN Tataba.